Travesty : the trial of Slobodan Milošević and the corruption of international justice - Laughland, John (Pluto Press, 2007)
-- A passionate critique of Milosevic's trial and the PR machine at the heart of international justice -- 'Study this story. ... The truth is hard to find, but in John Laughland we are fortunate to have a man blessed with the freedom to seek all facts, an.